Dietary diversity score and cardiovascular risk factors in Tehranian adults - Leila Azadbakht; Parvin Mirmiran; Ahmad Esmaillzadeh; Fereidoun Azizi (2006)
Abstract Aim To evaluate the relationship between dietary diversity score (DDS) and cardiovascular risk factors in Tehranian adults. Methods In this population-based cross-sectional study, a representative sample of 581 subjects (295 males and 286 females) aged over 18 years, residents of Tehran, participated. Hypercholesterolaemia, hypertriglyceridaemia and low high-density lipoprotein cholesterol were defined according to the Adult Treatment Panel III guidelines of the National Cholesterol Education Program. Diabetes was defined as fasting plasma glucose concentration ≥ 126 mg dl −1 or 2-h post challenge glucose concentration ≥ 200 mg dl −1 . Hypertension was defined on the basis of the sixth report of the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure. Dietary diversity was defined according to the Diet Quality Index revised. Results Mean (±standard deviation) DDS was 6.15 ± 1.02. The probability of having diabetes (odds ratio (OR) among quartiles: 1.45, 1.26, 1.11 and 1.00, respectively; P for trend = 0.04) and hypertriglyceridaemia (OR = 1.41, 1.23, 1.05 and 1.00, respectively; P for trend = 0.04) decreased with increasing quartile of the diversity score for whole grains. The probability of having obesity (OR among quartiles: 1.39, 1.06, 1.03 and 1.00, respectively; P for trend = 0.03), hypercholesterolaemia (OR = 1.46, 1.28, 1.11 and 1.00, respectively; P for trend = 0.03), hypertension (OR = 1.32, 1.17, 1.13 and 1.00, respectively; P for trend = 0.03) and high low-density lipoprotein cholesterol (LDL-C) (OR = 1.25, 1.12, 1.07 and 1.00, respectively; P for trend = 0.04) decreased with increasing quartile of the diversity score for vegetables. The probability of having hypercholesterolaemia, high LDL-C, hypertension and diabetes decreased with quartile of the DDS. But the probability of being obese increased with quartile of the DDS ( P for trend = 0.03). Conclusion DDS was inversely associated with cardiovascular risk factors in this cross-sectional study. Increased diversity scores of diets, to increase the variety score for vegetables, may be emphasised in programmes attempting to bring about changes in lifestyle.